Optimisme dan Peluang Dalam Menghadapi Masyarakat Ekonomi Asean (MEA) - Oscarius Yudhi Ari Wijaya (Fakultas Ekonomi Universitas 45 Surabaya, 2015)
The era of the free flow for goods, investments, services, capitals and labors has just arrived. There are two reactions of Indonesians to overcome it i.e. optimistic and pessimistic. Pessimistic reaction is coming together with those who are not ready, but not the opposite. Indonesians need to be more optimist as long as they have competitive advantage and being a specialist in some commodities (Comparative Advantage). There are so many opportunities in AEC for Indonesia, for example in tourism business. Basically AEC is not only to increase the aggregate transactions amongst its members but it also enlarging the market size. AEC is also here now with non-financial benefits e.g. knowledge enrichment, better foreign language skills and networking. This article is trying to say that AEC is not a threat but it’s an opportunity